Anatomical and physiological connectivity of the basal ganglia-thalamocortical motor circuit - Berry, N (2021)
The motor thalamus is a crucial component of the mammalian motor circuit which links subcortical sensorimotor inputs with cortical regions to facilitate ongoing control of movement and behaviour. Thalamocortical neurons from basal ganglia-recipient thalamus (BZ) and cerebellar-recipient thalamus (CZ) preferentially target different layers of motor cortex in rodents. Higher order BZ, comprised of ventral anterior (VA) and ventral medial (VM) thalamic nuclei innervate layer 1 (L1) of frontal cortical areas including motor cortex, and first order CZ, formed of ventral lateral thalamus (VL), innervates deeper layers. The prevailing assumption has been that pyramidal apical tuft dendrites are the exclusive postsynaptic target of BZ axons in L1. However, recent evidence has suggested that L1 elongated neurogliaform cells (ENGCs), which mainly reside in L1a and can be identified by expression of neuron-derived neurotrophic factor (NDNF), are directly targeted by higher order thalamic nuclei in prefrontal cortex and sensory cortical areas.